1 Records of the Governor and Company of the Massachusetts Bay 190 (Nathaniel B. Shurtleff ed., 1853) - (:unkn) unknown (My University, 1636)
Ordered that no person shall travel to Plymouth without some arms.
Keywords: REQUIRED POSSESSION